2018
DOI: 10.3389/fphys.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Vascular Changes Affect Turbulence in Aortic Blood Flow

Abstract: Turbulent blood flow is implicated in the pathogenesis of several aortic diseases but the extent and degree of turbulent blood flow in the normal aorta is unknown. We aimed to quantify the extent and degree of turbulece in the normal aorta and to assess whether age impacts the degree of turbulence. 22 young normal males (23.7 ± 3.0 y.o.) and 20 old normal males (70.9 ± 3.5 y.o.) were examined using four dimensional flow magnetic resonance imaging (4D Flow MRI) to quantify the turbulent kinetic energy (TKE), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 44 publications
1
44
0
1
Order By: Relevance
“…In another search of countermeasures to prevent retinal lesions elicited by microgravity, Lulli et al [ 116 ] exploited the antiapoptotic activity of coenzyme Q10 (CoQ10). Previous data have shown that CoQ10, by its ability to hinder mitochondrial depolarisation, effectively inhibits apoptosis of corneal keratocytes subjected to laser-based irradiation [ 117 , 118 ].…”
Section: Impact Of Microgravity On Apoptosis In Different Cell Typmentioning
confidence: 99%
See 1 more Smart Citation
“…In another search of countermeasures to prevent retinal lesions elicited by microgravity, Lulli et al [ 116 ] exploited the antiapoptotic activity of coenzyme Q10 (CoQ10). Previous data have shown that CoQ10, by its ability to hinder mitochondrial depolarisation, effectively inhibits apoptosis of corneal keratocytes subjected to laser-based irradiation [ 117 , 118 ].…”
Section: Impact Of Microgravity On Apoptosis In Different Cell Typmentioning
confidence: 99%
“…Previous data have shown that CoQ10, by its ability to hinder mitochondrial depolarisation, effectively inhibits apoptosis of corneal keratocytes subjected to laser-based irradiation [ 117 , 118 ]. Furthermore, results from ground experiments showed that CoQ10 prevents simulated microgravity–induced apoptosis and cytoskeleton alterations in human RPE (ARPE-19) cells [ 116 ]. In an ongoing study, ARPE-19 cells treated with or without CoQ10 were subjected to the space environment onboard the ISS for 72 h. The results from this study, including the assessment of the apoptosis rate, cytoskeletal morphology, telomere integrity and length, and the whole sequence analysis of RNA and DNA, are yet to be published.…”
Section: Impact Of Microgravity On Apoptosis In Different Cell Typmentioning
confidence: 99%
“…This work shows a shear-thinning rheology can explain the delayed transition for whole blood seen in published experimental data, but this delay is not the full story. The results show that, to accurately model transitional blood flow, and so enable the design of advanced cardiovascular devices, it is essential to incorporate the shear-thinning rheology, and to explicitly model the turbulent eddies.Fluids 2020, 5, 57 2 of 27 patients with no pathological diseases [4,5]. 4D MRI flow data indicated an increase in turbulent kinetic energy (TKE) of 73% in the aorta of older patients compared to younger patients which was determined to be related to area dilation of the aorta due to vascular ageing.…”
mentioning
confidence: 99%
“…Fluids 2020, 5, 57 2 of 27 patients with no pathological diseases [4,5]. 4D MRI flow data indicated an increase in turbulent kinetic energy (TKE) of 73% in the aorta of older patients compared to younger patients which was determined to be related to area dilation of the aorta due to vascular ageing.…”
mentioning
confidence: 99%
“…De acordo com o levantamento bibliográfico realizado nesta tese, a técnica 4D-flow é utilizada para auxiliar a conhecer o desempenho hemodinâmico na aorta nas seguintes circunstâncias: i) após a instalação de uma prótese valvar (Von Knobelsdorff-Brenkenhoff et al, 2014;Collins et al, 2015;Trauzeddel et al, 2016;Van Kesteren et al, 2018); ii) após o procedimento cirúrgico stent-enxerto (V-SARR) (Semaan et al, 2013;Stephens et al, 2015;Keller et al, 2016); iii) na presença da valva aórtica tricúspide saudável ou valva aórtica bicúspide (Von Knobelsdorff-Brenkenhoff et al, 2014;Garcia et al, 2015;Mirabella et al, 2015;Von Spiczak et al, 2015;Ha et al, 2018;Masutani et al, 2018;Raghav et al, 2018;Shen et al, 2018); iv) seguimento da evolução do aneurisma na aorta (Canstein et al, 2008;Callaghan et al, 2015;Collins et al, 2015;Masutani et al, 2018;Shen et al, 2018) e v) caracterização da doença aterosclerótica na aorta (Harloff et al, 2013;Markl et al, 2013).…”
Section: 11estudos In Vivounclassified